New Insights into the Biology of the Emerging Tembusu Virus - Rodolphe Hamel; Thipruethai Phanitchat; Sineewanlaya Wichit; Ronald Enrique Morales Vargas; Jiraporn Jaroenpool; Cheikh Tidiane Diagne; Julien Pompon; Dorothée Missé (Pathogens, 2021)
Reported for the first time in 1955 in Malaysia, Tembusu virus (TMUV) remained, for a long time, in the shadow of flaviviruses with human health importance such as dengue virus or Japanese encephalitis virus. However, since 2010 and the first large epidemic in duck farms in China, the threat of its emergence on a large scale in Asia or even its spillover into the human population is becoming more and more significant. This review aims to report current knowledge on TMUV from viral particle organization to the development of specific vaccines and therapeutics, with a particular focus on host-virus interactions.